PENGARUH KEPUASAN GAJI, SHIFT KERJA MALAM DAN KEPUASAN KERJA TERHADAP INTENSI KELUAR KARYAWAN (Studi pada Call Center PT Vads Indonesia Kantor Cabang Yogyakarta) - Farlianto Farlianto Farlianto (Universitas Negeri Yogyakarta, 2014)
High rate of turnover leads to adverse effect to an organization. Such problem is likely generating instability and uncertainty towards employment condition and human resources cost rise in forms of training invested to them, recruitment and newly built training programs. High turnover, in addition, also results in organizational ineffectiveness because it loses experienced employees as well as spends much times in training new, inexperienced employees.This study aims to analyze the effect of pay satisfaction, night shift work, and work on turnoverx intention. Samples that used in this research are 76 call center of PT Vads Indonesia employees with using simple random sampling, method data analysis used are multiple linear regression analysis, using SPSS program.Results of hypothesis testing, shows that the variables: the pay satisfaction has negative influence on turnover intention, night shift work has negative influence on job satisfaction, night shift work has positive influence on turnover intention, work satisfaction has negative influence on turnover intention and job satisfaction partially mediates between night shift work on turnover intention.